2019
DOI: 10.7717/peerj.6584
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and responses of antioxidant systems to dibutyl phthalate in neonate and adultDaphnia magna

Abstract: Dibutyl phthalate (DBP) poses a severe threat to aquatic ecosystems, introducing hazards to both aquatic species and human health. The ecotoxic effects of DBP on aquatic organisms have not been fully investigated. This study investigates acute toxicity, oxidative damage, and antioxidant enzyme parameters in neonate and adult Daphnia magna exposed to DBP. The obtained results show comparable DBP toxic responses in neonates and adults. The median lethal concentrations (LC50) of DBP in neonates exposed for 24 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 64 publications
(99 reference statements)
2
5
0
Order By: Relevance
“…Probably, different species (fish, zooplankton) and their sizes would have different sensitiveness to one pollutant and toxicity of one pollutant could be strongly regulated by some environmental conditions which are not similar in the laboratory and in situ. The calculated SC values for neonate and adult D. magna (0.56 and 0.98 mg dibutyl phthalate L -1 , respectively) were provided Shen et al (2019) after testing for max 94h, however, the authors did not discuss on their SC results. While this calculation seems A c c e p t e d m a n u s c r i p t useful for acute toxicity testing, it has its limits for whole life cycle, hence population relevant outcomes Further investigations to determine the SC of cyanobacterial compounds to microcrustaceans would need to include measures for a whole life cycle to ensure survival at individual and population levels.…”
Section: Acute Effects Of Dissolved Mcs On D Lumholtzimentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, different species (fish, zooplankton) and their sizes would have different sensitiveness to one pollutant and toxicity of one pollutant could be strongly regulated by some environmental conditions which are not similar in the laboratory and in situ. The calculated SC values for neonate and adult D. magna (0.56 and 0.98 mg dibutyl phthalate L -1 , respectively) were provided Shen et al (2019) after testing for max 94h, however, the authors did not discuss on their SC results. While this calculation seems A c c e p t e d m a n u s c r i p t useful for acute toxicity testing, it has its limits for whole life cycle, hence population relevant outcomes Further investigations to determine the SC of cyanobacterial compounds to microcrustaceans would need to include measures for a whole life cycle to ensure survival at individual and population levels.…”
Section: Acute Effects Of Dissolved Mcs On D Lumholtzimentioning
confidence: 99%
“…The authors suggested the SC value based on the 48h-LC50 multiplied with an application factor of 0.01 -0.04. Recently, Shen et al (2019) calculated SC for D. magna exposed to the dibutyl phthalate basing on the 24h-and 48-LC50 values and the application factor of 0.3. We will calculate SC for the investigated toxins and evaluate it in terms of life trait consequences.…”
Section: Introductionmentioning
confidence: 99%
“…A very limited number of studies with organisms as the target, dealing with acute phthalate toxicity, can be found in the scientific literature, using Vibrio fischeri [ 32 , 33 ], Danio rerio [ 34 ] , and Daphnia magna [ 35 , 36 ], all little focused on long-term exposures and the observation of abnormalities in the behavior of the target organism. Studies on the toxic effects of phthalates in humans carried out in vitro as also the results obtained with animals, show that the adverse effects observed are related to the reproductive system, compromised spermatic functions [ 37 , 38 ], embryonic toxicity [ 39 ]; ocular irritation [ 40 ], and changes in the blood cell constituents [ [41] , [42] , [43] ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this symptomatology was not subsequently found in the experimentation carried out on non-human primates [14]. Alterations of the hormonal system with contrasting effects (endocrine disruptors) have been highlighted both on rats and on primates [15][16][17][18]. Finally, it should be considered that plasticizers such as phthalates are largely involved in packaging process [19,20] and have been found in different food matrices [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%